PENGARUH LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DI DINAS KOPERASI UKM KOTA MAKASSAR - Sri Wahyuni; Samsul Rizal; Nurinaya (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the effect of work environment and organizational culture on employee performance at the Department of Cooperatives and SMEs, Makassar City. A quantitative approach was employed with a total population and sample of 78 employees through total sampling. Data were collected via a Likert scale questionnaire (1–5) and analyzed using multiple linear regression with SPSS. The results show that work environment has a positive and significant effect on employee performance (β=0.377; t=5.027; sig.=0.000), thus H1 is accepted. Organizational culture also has a positive and significant effect on employee performance (β=0.344; t=5.329; sig.=0.000), thus H2 is accepted. Simultaneously, both variables significantly affect employee performance (F=24.822; sig.=0.000). The coefficient of determination (R²=0.398) indicates that 39.8% of the variation in employee performance is explained by both variables, while the remaining 60.2% is attributed to other factors outside this model.